AES+F - Hou, Hanru 1963-; McGowan, Brooke Lynn 1981-; Morton, Tom 1977-; Ryan, Tina Rivers; Iacobelli, Natalia; Notini, S. (Rizzoli, 2022)
Since 1987, AES+F have been working at the intersection of painting, sculpture, photography, video, and new technologies. They achieved worldwide acclaim in the Russian Pavilion at the 52nd Biennale di Venezia in 2007 with their provocative, other-worldly Last Riot (2007), the first of their signature large-scale, multichannel video installations. Always pushing the boundaries of their practice, between 2016 and 2019 the collective also worked on video set designs for theater and opera. The volume will shed light on the psychoanalytic approach that underlies their language and provocations, intended to induce a process of self-reflection in the viewer, changing their perception of the world and society. Their visual journey will be articulated into three chronological sections corresponding to the most significant shifts in their conceptual evolution, covering their practice from 1995 to 2020
Keywords: AES+F -- Künstlervereinigung; Geschichte 1995-2020; AES + F (Group of artists) / https://isni.org/isni/000000012214736X; Art, Russian; Video art / 21st century; Video installations (Art) / 21st century; Photography, Artistic / 21st century; Installations (Art) / 21st century; Computer art / 21st century; Art russe; Art vidéo / 21e siècle; Installations vidéo (Art) / 21e siècle; Photographie artistique / 21e siècle; Installations (Art) / 21e siècle; AES + F (Group of artists); Bildband